Nuclear factor of activated T cells - a transcription factor family as critical regulator in lung and colon cancer - Daniel, Carolin; Gerlach, Katharina; Vaeth, Martin; Neurath, Markus; Weigmann, Benno (International Journal of Cancer, 2014)
Nuclear factor of activated T cells (NFAT) was first identified as a transcription factor which is activated upon T cell stimulation. Subsequent studies uncovered that a whole family of individual NFAT proteins exists with pleiotropic functions not only in immune but also in nonimmune cells. However, dysregulation of NFAT thereby favors malignant growth and cancer. Summarizing the recent advances in understanding how individual NFAT factors regulate the immune system, this review gives new insights into the critical role of NFAT in cancer development with special focus on inflammation-associated colorectal cancer.
EVALuna2:1902